Pelagodes cancriformis, a new emerald moth species from the north of Thailand, Laos and southern China (Lepidoptera, Geometridae: Geometrinae) - Viidalepp, Jaan; Lindt, Aare; Han, Hongxiang (Zootaxa, 2012)
Guenée (1858) described the genus Thalassodes for T. pilaria Guenée from Loyality Island (Tahiti) and some allied species. Prout (1912) revised the genus, listing 32 taxa from the Old World, and later (Prout 1933) listed forty species and divided Thalassodes into four unnamed sections according to habitus and structure of the male legs. Holloway (1996) divided Thalasssodes into three genera using genitalic charactersa and grouped 16 species in genus Pelagodes Holloway (type species: Thalassodes aucta Prout, 1912). Scoble (1999) attributed 22 species to the genus. Later, Inoue (2003, 2005, 2006) revised collections from the Oriental region, describing ten additional species and a further distinct genus, Reniformvalva Inoue, 2006. Han and Xue (2011) added four new species to Pelagodes and found external similarities between P. clarifimbria and moths from Hainan in China, but postponed any differentiation due to limited material. Lindt, while identifying his emerald moths collected in Laos, noticed genitalic differences between brown-fronted Pelagodes specimens from Laos and Thailand, which are allopatric in Thailand. Here we present a comparative description of P. clarifimbria and a new species P. cancriformis. Institutional acronyms are as follows:. EMNH, Estonian Museum of Natural History, Tallinn, Estonia. IZBE, formerly in Institute of Zoology and Botany of the Estonian Academy of Sciences, now deposited in Estonian University of Life Sciences, Tartu, Estonia. IZCAS, Institute of Zoology, Chinese Academy of Sciences, Beijing, China.